Local Wisdom Community in Fisheries Resource Utilization and Conservation In Korong Duku Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency, West Sumatera Province - Gusri Wahyuni; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted on 25th May - 8th June, 2013 in Korong Duku Pilubang Nagari Padang, Sungai Limau District, Padang Pariaman Regency, West Sumatera Province. This study used qualitative method with a phenomenological approach. Informants were selected by purposive sampling technique. Key informant was community leaders while supporters informants was public community, intelectual people and goverment who have known information in this research. Fishing ban tradition (malapeh niek ban fish) in Korong Duku Pilubang was motivated by economic Nagari society and fishieris resources condition was poor is felt more and more alarming. Development of local wisdom purposed to rehabilitate fishieris resources condition with kept type and amount of fish. By applied sanction, norms and moral values in the local wisdom.Keywords: Local Wisdom, Rivers, Fish Ban